Effective Communication Of The Family Assistance Team (TPK) In Preventing Stunting To Brides-To-Be In Air Napal Sub-District - Putri, Neni Pahmi; Narti , Sri; Sari , Sapta (Social Sciences Journal, 2024)
This research aims to find out the dangers of stunting and its prevention to prospective brides (catin). One of the things done is communication between the Family Assistance Team (TPK) and prospective brides (catin) through three (3) months of premarital assistance in Air Napal District. This research method is descriptive qualitative. The theory used is Cutlip and Allen's effective communication process theory, namely credibility, context, content, clarity, sustainability, media and understanding. The results showed that the effective communication process consists of credibility, context, content, clarity, sustainability, media and understanding as follows: The Family Assistance Team (TPK) succeeded in building strong credibility so that prospective brides (catin) were interested in exploring information related to stunting prevention. Furthermore, context, the family assistance team (TPK) provides real and directed communication, information and education related to stunting prevention. Content, through the ELSIMIL application, catin can access educational content related to stunting prevention and pregnancy readiness. Clarity (clear message), the process of communication and delivery of education related to stunting and its prevention is clear and easily understood by catin. Continuity of communication that takes place even when the catin is married, pregnant and becomes a post-saline mother. The media are social media whatsaap and facebook which are very effectively used by the Family Assistance Team (TPK) and prospective brides (catin). Furthermore, understanding, namely both parties can be said to have carried out effective communication with the same understanding or the message conveyed can be received and applied properly. The occurrence of effective communication is also because the Family Facilitating Team and the bride-to-be (catin) already know each other well so as to increase the trust of the bride-to-be (catin) in the Family Facilitating Team (TPK).